Spór o "ciemność" - Mitzner, Piotr; Czapski, Józef (Colloquia Litteraria, 2020)
The publication presents the polemic that started in the Paris ‘Kultura’ in 1975 and in private correspondence after the publication of the article “Laur i Ciemność” by Maciej Broński (Wojciech Skalmowski) about Cyprian Norwid. Józef Czapski and Witold Wirpsza took part in the dispute. Skalmowski, following the trail of former critics of Norwid, accused him of incomprehensibility, Czapski and Wirpsza strongly rejected his arguments.